1994
DOI: 10.5558/tfc70731-6
|View full text |Cite
|
Sign up to set email alerts
|

Community forestry in developed and developing countries: A comparative study

Abstract: Concerns about the ecological and economic sustainability of La probltrnatique entourant la durabilit6 hlogique et konomique industrial forestry led to the revival of community forestry (CF) de la foresterie industrielle a provoqut la renaissance de la in the developing countries. Recently, the developed countries are foresterie communautaire (FC) dans les pays en voie de developpealso examining the feasibility of CF as a land management alterment. Les pays dtvelopp6s se sont depuis peu pencht sur la posnati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…These observations are in line with typical goals of community forestry in the developed world. As Mallik and Rahman (1994) explain, community forests in developed countries are usually large, capital intensive and market oriented.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations are in line with typical goals of community forestry in the developed world. As Mallik and Rahman (1994) explain, community forests in developed countries are usually large, capital intensive and market oriented.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…They concluded that finding common criteria for success in different sites is difficult, as each community was successful for different reasons. Mallik and Rahman (1994) compared opportunities and challenges for community forestry in developed and developing countries. They concluded that community forestry in developing countries was generally small, labour-intensive, and geared towards meeting the basic needs of the community people while in developed countries, the communities operated on a larger scale, with more capital and more of a market orientation.…”
Section: Study Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementing this wide range of objectives is an equally wide variety of situations referred to as community forests -they exist in all sizes, ownerships, forest types, management structures, and silvicultural strategies, to name but a few important dimensions. And they exist around the world, differing markedly between developed and developing countries (Mallik and Rahman 1994).…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by Mallik & Rahman (1994), the land tenure arrangement is a critical factor in developing a successful community forestry project. Despite the Sloan Royal Commission (1956) recommendation for change in existing tenure arrangement such as TFLs, the same tenure system still exists and is held not only by industrial based forestry companies, but also by some of the well-known community based forestry projects in BC.…”
mentioning
confidence: 99%